The functional-semantic features of phraseological units containing words with the etymon god- in the Russian language - Yu.K. Lukoyanova (Ученые записки Казанского университета: Серия Гуманитарные науки)
The paper deals with the functioning of phraseological units (idioms and set expressions), which include words with the etymon god- (год- 'year'), in the Russian language. The purpose of the research is to trace the semantic transformations of lexemes with the etymon god-, as part of phraseological units, and to study the features of using phraseological units with the specified words. To fulfill this purpose, phraseological units containing the studied words have been identified, their dictionary definitions have been analyzed, and their stylistic properties have been characterized. The data of the study have been taken from phraseological, explanatory, historical dictionaries and the National Corps of the Russian language. Based on the obtained results, the information on the etymological nest with the etymon god- has been completed and the semantic evolution of the studied words has been demonstrated. Firstly, the inner form of phraseological units reflects the views of our ancestors on the world order, including those that concern the time (kruglyi god (круглый год 'the year round'), bez godu nedelya (без году неделя 'for a short time')). Secondly, the phraseological units retain words with the lost meanings (chernyi god (чёрный год 'evil year'), zhdat' u morya pogody (ждать у моря погоды 'indulge in vain hopes'). Such words as ugoda (угода 'complaisance'), ugodnost' (угодность 'obligingness') disappeared, they are found only in the phraseological units v ugodu (в угоду 'in order to please'), v ugodnost' komu (в угодность кому 'to please'), the word ugodno (угодно 'desired') has lost its semantics and now is used only as part of the set expressions esli ugodno, kak vam ugodno (если угодно, как вам угодно 'as you please'). The examples of synonymy, antonymy, enantiosemy of phraseological units containing words with the etymon god- in the Russian language have been provided. The author's use of phraseological units by writers has been revealed. The hypothesis about the appearance of a new idiom погода в доме has been introduced. On the whole, the research allows to draw a conclusion that the use of words with the etymon god- in phraseological units, on the one hand, allows preserving their ancient semantics and, on the other hand, can contribute to their de-etymologization. The results of the research can be used in teaching courses on historical lexicology, phraseology, and etymology.